2003
DOI: 10.1073/pnas.0437993100
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of short nucleotide sequences that affect translation initiation in Saccharomyces cerevisiae

Abstract: In previous studies, we demonstrated the sufficiency of short nucleotide sequences to facilitate internal initiation of translation in mammalian cells. By using a selection methodology, we have now identified comparable sequences in Saccharomyces cerevisiae. For these studies, a library of constructs expressing dicistronic mRNAs with the HIS3 gene as the second cistron and 18 random nucleotides in the intercistronic region was introduced into a yeast strain in which the endogenous HIS3 gene was deleted. Untran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…When tested in isolation these relatively short sequences enhanced the translation of a second cistron in a dicistronic mRNA (1,2). In addition, we found that RNA sequences with IRES activity could be selected from libraries of random 9-to 18-nt sequences (3,4). Although in most cases, IRES activity mediated by an individual IRES element was relatively weak, it could be greatly enhanced when multiple copies of some of the individual IRES elements were linked together in tandem (1,3).…”
mentioning
confidence: 89%
“…When tested in isolation these relatively short sequences enhanced the translation of a second cistron in a dicistronic mRNA (1,2). In addition, we found that RNA sequences with IRES activity could be selected from libraries of random 9-to 18-nt sequences (3,4). Although in most cases, IRES activity mediated by an individual IRES element was relatively weak, it could be greatly enhanced when multiple copies of some of the individual IRES elements were linked together in tandem (1,3).…”
mentioning
confidence: 89%
“…RNA folding programs such as MFOLD (31) predict that this sequence exhibits little, if any, structure. There have been reports of short sequences of between 9 and 22 nt that can serve as IRESs (32)(33)(34)(35). Unlike the tk IRES, these sequences were analyzed in reporter constructs that placed the test sequence in close proximity to the AUG of the downstream reporter gene.…”
Section: Discussionmentioning
confidence: 99%
“…The present development of a feedback method to identify individual IRES elements is an extension of our earlier studies (20,22) and is motivated by the possibility that short sequences, such as the 7-nt Gtx IRES module are widespread within the mRNA population and that combinations of these mRNA sequences may have important global effects on the proteome. The development of an efficient selection method to identify IRES elements will enable their sequences to be characterized on the basis of sequence motifs and expression properties; it will also enable an assessment of the frequency of these elements in the messenger population.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, we generated synthetic IRESes containing multiple individual IRES elements and showed that this multimerization led to higher, and in some cases exponential, increases in IRES activity. To facilitate the discovery process, we and others have developed a number of methods to screen for IRES elements in mammalian cells (20,21) and in yeast (22). In all of these studies, dicistronic mRNAs containing a library of random nucleotide sequences in the intercistronic sequence (ICS) were expressed in cells, and those cells containing IRES elements were identified on the basis of the expression of the second cistron.…”
mentioning
confidence: 99%